SSDAlloc: Hybrid RAM/SSD Memory Allocation Made Easy - Badam, Anirudh; Pai, Vivek (Symposium on Networked Systems Design and Implementation (NSDI'11), 2011)
We introduce SSDAlloc, a hybrid main memory management system that allows developers to treat solid-state disk (SSD) as an extension of the RAM in a system. SSDAlloc moves the SSD upward in the memory hierarchy, usable as a larger, slower form of RAM instead of just a cache for the hard drive. Using SSDAlloc, applications can nearly transparently extend their memory footprints to hundreds of gigabytes and beyond without restructuring, well beyond the RAM capacities of most servers. Additionally, SSDAlloc can extract 90% of the SSD’s raw performance while increasing the lifetime of the SSD by up to 32 times. Other approaches either require intrusive application changes or deliver only 6–30% of the SSD’s raw performance.